Dysregulated pathways in plasmacytoid dendritic cells involved in systemic sclerosis-associated interstitial lung disease - Simões, Raquel dos Anjos Dias (2023)
Systemic sclerosis (SSc) is an autoimmune disorder characterised by microvascular damage and fibrosis of the skin and internal organs, including the lung. Interstitial lung disease (ILD), which is characterised by lung fibrosis, is the leading cause of mortality in SSc. Plasmacytoid dendritic cells (pDCs) are critical cellular mediators that promote lung fibrosis through unknown mechanisms. The technology of single-cell RNA sequencing (scRNA-seq) allows analysis of gene expression at the single-cell level. Through the study of the transcriptome of pDCs, dysregulated pathways involved in fibrosis progression may be explored. The goal of this study was to identify differential gene expression in pDCs between samples from healthy control donors and patients with SSc. For that, two publicly available datasets that include samples from individuals with SSc were bioinformatically analysed. One was constituted by samples of patient’s lungs (n=13) and the other by samples of skin (n=412) and blood (n=147). After bioinformatic analysis of data obtained from the lung, 34 pDCs were identified, only in patient samples. Considering the skin/blood dataset, 119 and 107 pDCs were identified in skin and blood samples, respectively. In these last two tissues, a higher percentage of pDCs was obtained in samples from patients that had ILD. A differential gene expression analysis was performed to each tissue sample comparing individuals and conditions. From skin and blood data no genes were found differentially expressed between control and patients. However, samples of lung from patient 1 were statistically different from samples from patients 3 and 4. Interestingly, pDCs from these later patients, which have usual interstitial pneumonia with prominent lymphoid aggregates, a more severe clinical phenotype, showed alterations in biological processes, such as translation, biosynthesis, rRNA binding and metabolic pathways; in the molecular functions, like inhibitory activity of ubiquitin-protein and RNA biding; and in cellular components, namely the cytosol, ribosomes, and reticulum endoplasmic. From this work, we can conclude that the number of pDCs present in each tissue is increased in samples of patients with SSc. Furthermore, some pathways related to translation, biosynthesis, metabolic processes, and RNA binding were found upregulated in pDCs of patients with increased disease severity.